Fibroqueratoma periungueal adquirido: tratamiento quirúrgico - López López, Daniel; López López, Luis; Barriuso Cao, Mónica; Álvarez-calderón Iglesias, Óscar; Fornos Vieitez, Benedicto (Revista Internacional de Ciencias Podológicas, 2007)
Acquired periungual fibrokeratoma is a benign fibroepitelial tumor, relatively common, but with minor incidence at the foot. It is characterized by presenting a fleshy mass covered with hyperpigmented skin and with hyperqueratosis in its distal portion, whose consistence is strong and "indurada" with a size that varies from 5 to 10 mm in length. Sometimes it can be painful after minor trauma or it can even bleed. In that case, surgical treatment can be suggested, as in the case reported. We present the case of a 31 years old patient, who comes to the office due to a painful isolated periungeal fibroma at the level of the third right toe, being recommended the surgical excision of the mass. Blood analysis and dorsolateral and dorsoplantar x-rays are required, to make sure that there´s no evidence of underlying bony pathology. The surgical technique has been carried out, under local anaesthesia making an elliptical incision following the lines of tension of the skin, and removing the fibroma. Sutures were necessary to heal the wound. After removing the mass, a biopsy was carried out and sent to the pathological anatomy department to ensure the diagnosis. The postoperative period was painless and the appearance of the toe was excellent. After one year follow-up, nor recurrences or associated problems appeared. We conclude that acquired periungual fibrokeratoma represents a well defined clinically and histologically benign tumor, easily diagnosed. The surgical approach appears to be as the best way to manage the situation definitively.